Dysrhythmic profile of drugs with a positive inotropic effect in patients with acute coronary syndrome. (3rd May 2023) - Carias, M; Almeida, A; Paralta, M; Claudio, F; Rocha, R; Bento, A; Trinca, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Patients with acute coronary syndrome (ACS) may develop ventricular dysfunction and need to use drugs with a positive inotropic effect during the acute phase. Despite the hemodynamic benefit of the use of these drugs, positive inotropic drugs may have several side effects. Among these, ventricular arrhythmias and atrial fibrillation. Levosimendan is a drug that increases the sensitivity of the myocardium to calcium, producing a positive inotropic effect. Purpose: This study aims to assess the frequency of occurrence of dysrhythmic complications with the use of positive inotropic drugs in patients hospitalized for ACS. Methods: We performed a 6-year retrospective, observational, multicenter study. We included patients with ACS who used positive or not inotropic drugs during hospitalization, dividing the sample into two groups respectively (Group 1 and Group 2). Between the two groups we compared the occurrence of ventricular tachycardia and atrial fibrillation. In addition, we performed an analysis for the use of levosimendan. Results: We analyzed a sample of 5860 patients. Of these, 70.3% were male. In Group 1 we included 377 patients and in Group 2 5329 patients. The occurrence of ventricular tachycardia in Group 1 was higher than in Group 2 (15.5% vs 1.6%; p<0.001; OR: 11.472; 95% CI [8.212;16.027]). The rate of occurrence of atrial fibrillation in Group 1 was higher than in Group 2 (19.3% vs 5.1%; p<0.001; OR:4.413; 95% CI [3.388;5.749]). Regarding the use of levosimendan, 50 patients were analyzed. Ventricular tachycardia was more frequent with the use of this drug than without it (18.0% vs 2.5%; p<0.001; OR: 8.576 95% CI [4.092;17.976]). Atrial fibrillation was more frequent with levosimendan use than with no use (34.0% vs 6.0%; p>0.001; OR: 8.137; 95% CI [4.487;14.754]). Conclusion: Arrhythmic complications were much more frequent in the group that used positive inotropic drugs, namely ventricular tachycardia and atrial fibrillation. Levosimendan stands out, related to the increase in the occurrence of atrial fibrillation and the remaining inotropes with an increased risk of ventricular tachycardia. These arrhythmic complications pose a challenge in the management of these patients.